Արցախի մշակութային ժառանգության օտարացման և յուրացման մեթոդաբանությունը Ադրբեջանի պատմագիտության մեջ - Սաֆարյան, Վարդգես (ԱրՊՀ հրատ․)
В статье выявляются политические и научные тенденции и методология азербайджанской исторической науки, направленные на фальсификацию древней и средневековой культуры Арцаха. The article identifies political and scientific trends and methodology of the Azerbaijani historical science, aimed at the falsification of the ancient and medieval culture of Artsakh.
Keywords: Արցախ; Մշակույթ; Պատմագրություն